Ghosts - Telgemeier, Raina (New York : Graphix, 2016)
Catrina and her family have moved to the coast of Northern California for the sake of her little sister, Maya, who has cystic fibrosis--and Cat is even less happy about the move when she is told that her new town is inhabited by ghosts, and Maya sets her heart on meeting one.
School Library Journal starred, June 2016.
Booklist starred, June 2016.
Pub Weekly, June 2016.
Kirkus Starred, July 2016.
Horn Book, September 2016.
Bulletin (Center for Children's books), July 2016.
Keywords: Sisters -- Comic books, strips, etc -- Fiction; Ghosts -- Comic books, strips, etc -- Fiction; Cystic fibrosis -- Comic books, strips, etc -- Fiction; Moving -- Comic books, strips, etc -- Fiction; Family life -- California -- Comic books, strips, etc -- Fiction; Sisters -- Juvenile fiction; Ghosts -- Juvenile fiction; Cystic fibrosis -- Juvenile fiction; Moving, Household -- Juvenile fiction; Family life -- California -- Juvenile fiction; California, Northern -- Comic books, strips, etc -- Fiction; California, Northern -- Juvenile fiction; Paranormal comics; Graphic novels; Graphic novels; Comics (Graphic works)